2009
DOI: 10.1007/s00586-009-0919-7
|View full text |Cite
|
Sign up to set email alerts
|

The narrowing of the lumbar spinal canal during loaded MRI: the effects of the disc and ligamentum flavum

Abstract: Load and activity changes of the spine typically cause symptoms of nerve root compression in subjects with spinal stenosis. Protrusion of the intervertebral disc has been regarded as the main cause of the compression. The objective was to determine the changes in the size of the lumbar spinal canal and especially those caused by the ligamentum flavum and the disc during loaded MRI. For this purpose an interventional clinical study on consecutive patients was made. The lumbar spines in 24 supine patients were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
90
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 19 publications
1
90
0
2
Order By: Relevance
“…In evaluating the severity of spinal canal narrowing, the dural sac cross-sectional area (DCSA) is frequently measured by using axial MR images. [1][2][3][4][5][6] However, conventional MR imaging is performed with the patient in the supine position, and the DCSA may be larger in this position than in the standing position. 3,4,7 Hence, conventional MR imaging carries a risk of underestimating the severity of spinal canal narrowing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In evaluating the severity of spinal canal narrowing, the dural sac cross-sectional area (DCSA) is frequently measured by using axial MR images. [1][2][3][4][5][6] However, conventional MR imaging is performed with the patient in the supine position, and the DCSA may be larger in this position than in the standing position. 3,4,7 Hence, conventional MR imaging carries a risk of underestimating the severity of spinal canal narrowing.…”
mentioning
confidence: 99%
“…Axial-loaded MR imaging may induce a significant reduction in the DCSA and potentially show additional imaging findings that cannot be acquired on conventional MR imaging. 3,4,6,8 The DCSA on axial-loaded MR imaging has been reported to correlate with the severity of clinical symptoms in patients with LSCS. 9 Furthermore, previous studies have demonstrated that a dynamic decrease in the DCSA induced by axial loading increases the diagnostic specificity of spinal canal narrowing and influences the indications for surgical treatment.…”
mentioning
confidence: 99%
“…Recently, some researchers have reported a device that can apply axial loading to the lumbar spine of patients in the supine position during MRI 10,[23][24][25][26] . Use of the device could induce significant narrowing of the spinal canal and provide valuable information that was not detected by conventional MRI [23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Use of the device could induce significant narrowing of the spinal canal and provide valuable information that was not detected by conventional MRI [23][24][25][26] . Kanno et al 27) described that the DCSA on axial-loaded MRI was significantly correlated with the severity of the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Domed disc has been recognized as a major cause of compression. Hansson et al [17] evaluated the change in the size of the lumbar spinal canal in patients with discectomy and bold ligamentum flavum. the authors concluded that an overload of the lumbar spine can produce changes in the intervertebral discs but also in the yellow ligaments which, likewise, are bulging, and are actively involved in the pathogenesis of spinal canal stenosis causing stenosis of up to 50-85%.…”
Section: Discussionmentioning
confidence: 99%